Sequência didática para aprendizagem ativa das Leis de Newton - Menezes, Luciene da Silva (2016)
Just as in other areas of knowledge, teaching physics remains focused on the content present in the manuals and textbooks. In this perspective, teachers tend to transmit the contents in just lectures and without presenting any connection with the daily life of students. They end up having a passive behavior in the process, often simply performing mathematical calculations instead of interpreting physical phenomena. In this educational product, I propose to physics teachers differently in addressing the Laws of Newton, avoiding the practice of traditional classes where the teacher requires the contents to be decorated by students only in order to pass the year. The methodology was developed in the State College João de Melo Prado - Divina Pastora, in a class of 1st year of high school. As a facilitator teaching tool learning, I made the use of educational resources as the figure titled "Where are the forces", showing the relationship between the forces and the change of momentum; the simulation of the PhET "Cape War" as interactive demo; conceptual issues such as "peer intruction"; building a dynamometer; view the episode "Pulleys (Sheaves)" the animated series "How it Works"; Experimental kit pulleys. As a way of evaluating the active learning took into account qualitative aspects such as student participation during the development of the activities, and quantitative aspects, through pre-test and post-test questionnaire. The results showed active learning by the students. The purpose of this Didactic Sequence is to enable students to understand the applications of Newton's laws in their day to day, dynamically, with active participation of them in the activities developed during application.